Cross-border trade and conservation in the Sangha river region (Cameroon, Central African Republic and Republic of Congo) - Koning, R.G. de; Tieguhong, J.C.; Amougou, V. (2007)
In Africa conservation areas are increasingly established along national borders where human activity seems low. In reality border areas are often vibrant places of economic interaction. This article looks at conservation opportunities and challenges posed by cross border natural resource trade in the Sangha River Region, which straddles the borders of Cameroon, the Central African Republic and the Republic of Congo. It argues that conservation projects and forestry administrations can and should contribute to trade liberalisation, thereby unlocking the economic potential in poor and remote forest areas. If accompanied with strict law enforcement in cases of major disruptive and illegal practices, policies in this direction can help to integrate development and conservation objectives.